Research on central sensitization of endometriosis-associated pain: a systematic review of the literature - Zheng, Ping (J Pain Res, 2019)
Endometriosis-associated pain afflicts an enormous number of women who suffer from endometriosis. There is an urgent need to explore the pathogenesis of endometriosis-associated pain to identify targets for treatment of hyperalgesia. A search was conducted in PubMed, Web of Science, Embase, and the Cochrane Library using the search terms “endometriosis” AND (“pain” OR “hyperalgesia” OR “nociception” OR “allodynia”) AND “central sensitization”. The search was limited to articles published in English from 01/01/2008 to the present. Among the search results, 15 articles were eligible for systematic review, including 6 reviews, 6 human studies (one in the form of a conference abstract only), and 3 animal studies. The articles were classified into 4 lists to describe the mechanism of endometriosis-associated pain and synthesize different aspects of research on it. In conclusion, there is a need to explore the mechanism of endometriosis-associated pain in terms of innervation, vascularization, local inflammation, cross-correlated visceral sensitization, and central sensitization to identify the target molecules and signaling pathways of key genes and relevant biomarkers through new techniques, all with the goal of developing a more comprehensive treatment strategy for endometriosis than is currently available.